2018
DOI: 10.1177/0961000618810378
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between job involvement, leader-member exchange, and innovative behavior of public librarians

Abstract: Public library leaders require librarians to exhibit markedly high job involvement and notably innovative behaviors to maintain pace with rapidly varying environments. The study examined the relationships between the job involvement, leader–member exchange, and innovative behavior of public librarians through structural equation modeling. The finding identified the antecedents (job involvement and leader–member exchange ) of innovation behavior. Leader–member exchange was a significant moderator of the job inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…This research also proved that job involvement significantly affects IWB, such that lecturers with high job involvement tend to have high IWB. It is consistent with the reports of Peng (2018), Huang et al (2019), andKundu et al (2020). This indicates that lecturers participating actively in their work tend to be passionate about formulating, experimenting, and evaluating ideas and solutions for real improvement.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This research also proved that job involvement significantly affects IWB, such that lecturers with high job involvement tend to have high IWB. It is consistent with the reports of Peng (2018), Huang et al (2019), andKundu et al (2020). This indicates that lecturers participating actively in their work tend to be passionate about formulating, experimenting, and evaluating ideas and solutions for real improvement.…”
Section: Discussionsupporting
confidence: 84%
“…The high level of these indicators increases lecturers' IWB, such that their work participation tends to be passionate about formulating, experimenting, and evaluating ideas and solutions to ensure improvement. Several research have also concluded that job involvement significantly affects IWB (Peng, 2018;Huang et al, 2019;Kundu et al, 2020), and this led to the formulation of the following hypothesis: H3: Job involvement has a direct effect on IWB.…”
Section: Job Involvement and Iwbmentioning
confidence: 99%
“…The organizations which serve as the object of the research contain research samples from the most part of public services [ [19] , [20] , [21] ], such as nurses [ 17 , 22 , 23 ], educators [ 24 ]. As well as librarians [ [25] , [26] , [27] , [28] ]. Likewise, the geographical locations of the research conducted vary from several continents, with the most research being conducted on the Asian continent (42.1%).…”
Section: Resultsmentioning
confidence: 99%
“…As claimed by Kanungo (cited in Eldor & Harpaz, 2018), job involvement means, "cognitive or belief state of psychological identification". Supposedly, individual's internal cognition of activity identities or beliefs is the foundation of job involvement (Peng, 2018;Robbins & Judge, 2018, p.50). Psychologically, people are identified by their job and work activity is supposed essential to self-concept (Welbourne & Sariol, 2017;Zagenczyk, & Murrell, 2009;Ho, 2006;Carson, Carson, & Bedeian 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Lambert, Qureshi, Frank, Klahm, & Smith (2018) proposed, when an individual places the job at the center of his life's interest, his job involvement takes a high degree. The well-known saying: 'I live, eat, and breathe my job' describes an individual whose job involvement is strongly high (Lambert et al, 2018;Peng, 2018;Yeh, 2018;Kong, 2013;Lambert, Minor, Wells, & Hogan, 2016;Nyambegera, 2000). Overall, self-accomplishment, positive and career-oriented psychological state are established by influential job involvement (Peng, 2018).…”
Section: Introductionmentioning
confidence: 99%